Coral reef fishes : dynamics and diversity in a complex ecosystem - Sale, Peter F. (Academic Press, 2002)
The Encyclopedia of Insects is a comprehensive work devoted to all aspects of insects, including their anatomy, physiology, evolution, behavior, reproduction, ecology, and disease, as well as issues of exploitation, conservation, and management. Articles provide definitive facts about all insects from aphids, beetles and butterflies to weevils and yellowjackets. Insects are beautiful and dreadful, ravenous pests and devastating disease vectors, resilient and resistant to eradication, and the source of great benefit and great loss for civilization. Important for ecosystem health, they have infl.